Effects of lumbosacral orthosis on dynamical structure of center of pressure fluctuations in patients with non-specific chronic low back pain: A randomized controlled trial. Issue 4 (October 2019) - Azadinia, Fatemeh; Ebrahimi-Takamjani, Ismail; Kamyab, Mojtaba; Asgari, Morteza; Parnianpour, Mohamad
Abstract: Background: A few clinical trials have examined the effect of treatment interventions on postural control in patients with chronic low back pain, all of which have exclusively evaluated postural stability using traditional linear measures of postural sway. However, postural control improvement cannot be determined by exclusively relying on linear measurements, because these parameters provide no information on underlying motor control mechanisms. Objective: This study aimed to compare the effect of using lumbosacral orthoses (LSO) together with routine physical therapy, compared to routine physical therapy alone on postural control, using nonlinear analysis techniques. Methods: Forty-four patients with low back pain were randomly allocated to the intervention and control groups. Both groups underwent 8 sessions of physical therapy twice weekly for 4 weeks. The intervention group received LSO in addition to routine physical therapy. Before and after the intervention, non-linear dynamical features of center of pressure fluctuations were assessed during quiet standing at 3 difficulty levels of postural tasks, including eyes open while standing on a rigid surface, eyes closed while standing on a rigid surface, and eyes closed while standing on a foam surface. Results: The results of this study showed that a 4-week intervention consisting of LSO and routine physical therapy modalities did not affect the temporal structure of postural sways in patients with low back pain. Conclusion: Treatment strategies, such as routine physical therapy modalities or LSO, which exclusively focus on the correction of peripheral mechanics, fail to affect the behavior of the postural control system.